Orde Subgrup Terkecil yang Memuat Suatu Himpunan dengan 2 Unsur dari Suatu Grup Hingga Siklik - Rasdin Sandria; Jufra Jufra; Norma Muhtar (UIN Imam Bonjol Padang, 2023)
Suppose is any group and then the smallest subgroup of containing is the intersection of all subgroups of containing and denoted by . If then , such a subgroup we know as a cyclic group with generator , such that the order of is the same as the order of . In this research, observations were made on the set in order to know the nature of the membership of and the order of for the case of order 2 and further for of order n if G is a cyclic finite group using the effect of Lagrange Theorem.